Ordinances and Joint Resolutions of the City of San Francisco; Together with a List of the Officers of the City and County, and Rules and Orders of the Common Council Page 220, Image 256 (1854) available at The Making of Modern Law: Primary Sources. - (:unkn) unknown (General Publisher, 1854)
Every person, house, or firm engaged in keeping a pistol or rifle shooting gallery, shall pay for a license to carry on the same, the sum of ten dollars per quarter, in addition to the amount of the powder license.
--
Keywords: SHOOTING RANGES OR GALLERIES